A novel configuration of a microstrip metamaterial reconfigurable bandstop filter - Aghanim, Amina; Oulhaj, Otman; Zbitou, Jamal; Oukaira, Aziz; Lakhssassi, Ahmed; Lasri, Rafik (Institute of Advanced Engineering and Science, 2024)
This paper presents the design, simulation, and test measurements of a microstrip bandstop filter operating at 1.5 GHz, incorporating six split ring resonator (SRR) unit cells. The substrate employed is an FR-4 with a thickness of 1.6 mm and tangent losses of 0.025. In the initial phase, the design is conceptualized, simulated using computer simulation technology (CST) studio and advanced design system (ADS) Agilent simulators, and validated through test measurements. Building upon this foundation, the filter is transformed into a reconfigurable variant by integrating four SMV2019 varactor diodes. These varactors are modeled to ensure the reconfigurability of the bandwidth. The integration of varactors introduces dynamic tuning capabilities to the considered bandstop filter.